Environmental crime and instability: the role of criminal networks in the trafficking and illegal dumping of hazardous waste - Valentina Baiamonte; Elise Vermeersch (Freedom from Fear, 2011)
Amongst environmental crimes, trafficking and illegal dumping of waste has become a significant source of revenue, attracting growing interest of unscrupulous brokers as well as criminal networks. This crime poses not only a serious prothreat to the environment and human health, but has also become one of the causes for social and economic instability.